On the Fourier transform and the exchange property - Dragu Atanasiu; Piotr Mikusiński (International Journal of Mathematics and Mathematical Sciences)
A simplified construction of tempered Boehmians is presented. The new construction shows that considering delta sequences and convergence arguments is not essential.